Health and functional benefits of yoga practice in times of the COVID-19 coronavirus pandemic - Olga Ilona Smoleńska; Marta Pilarska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
The purpose of this article is to identify and quantify the benefits of yoga practice, particularly in the most severe of the coronavirus pandemic and related lockdown periods. The subject of the research was the form and quality of online yoga practice, which has become an alternative to sports and stationary activities. The most important health benefits of yoga practice are also discussed. Using the method of analysis of documents and sources, the role and importance of yoga in the health context and its advantages related to maintaining health during the coronavirus pandemic have been demonstrated. The authors of the publication also made an original quantitative and qualitative analysis of individual forms of online yoga practice, according to the most popular and used tools and technologies in this discipline. An analysis of functionalities conducted on Facebook and Instagram social networking sites, live broadcasts, applications that can be installed on smartphones and channels on the YouTube website, publishing videos for joint yoga practice, was developed. Using own observation and SWOT analysis, all the strengths and weaknesses of online yoga practice, as well as its opportunities and threats, were presented.